(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the socio-legal and cultural significance of religious offices during the period of the Bukhara Emirate based on the "Qushbegi Archival Documents" held at the Central State Archive of Uzbekistan. The study highlights the role of religious institutions within the Emirate’s administrative system, the procedures for appointing officials such as muftis, imams, mudarrises, and shaykhs, and the formal administrative interactions between the Amir, the Qushbegi, and the Qozikalon. Through a systematic classification and comparative analysis of archival records, the article provides scholarly insights into the influence of religious authorities on state policy and the spiritual life of society